Sporoderm-Broken Spores of Ganoderma lucidum Sensitizes Ovarian Cancer to Cisplatin by ROS/ERK Signaling and Attenuates Chemotherapy-Related Toxicity - Cen, Kaili; Chen, Ming; He, Mengye; Li, Zhenhao; Song, Yinjing; Liu, Pu; Jiang, Qi; Xu, Suzhen; Jia, Yunlu; Shen, Peng (Frontiers in Pharmacology, 2022)
Although platinum-based chemotherapeutics such as cisplatin are the cornerstone of treatment for ovarian cancer, their clinical application is profoundly limited due to chemoresistance and severe adverse effects. Sporoderm-broken spores of Ganoderma lucidum (SBSGL) have been reported to possess antitumor effects. However, the function and mechanism of SBSGL and its essential composition, ganoderic acid D (GAD), in the cisplatin therapy on ovarian cancer have yet to be investigated. Here, we investigated the combined effect of SBSGL and cisplatin in an ovarian tumor xenograft model. The results showed that combining SBSGL with cisplatin reduced tumor growth and ameliorated cisplatin-induced intestinal injury and myelosuppression. We also confirmed that GAD could enhance the therapeutic effect of cisplatin in SKOV3 and cisplatin-resistant SKOV3/DDP cells by increasing the intracellular reactive oxygen species (ROS). Mechanistically, we proved that ROS-mediated ERK signaling inhibition played an important role in the chemo-sensitization effect of GAD on cisplatin in ovarian cancer. Taken together, combining SBSGL with cisplatin provides a novel therapeutic strategy against ovarian cancer.